Improvement in oxygen evolution performance of NiFe layered double hydroxide grown in the presence of 1T-Rich MoS2 - Chakraborty, Soumita; Marappa, Shivanna; Agarwal, Sakshi; Bagchi, Debabrata; Rao, Ankit; Vinod, Chathakudath P.; Peter, Sebastian C.; Singh, Abhishek; Eswaramoorthy, Muthusamy (ACS Applied Materials & Interfaces, 2022)
NiFe layered double hydroxide (NiFe LDH) grown in the presence of MoS2 (rich in 1T phase) shows exceptional performance metrics for alkaline oxygen evolution reaction (OER) in this class of composites. The as-prepared NiFe LDH/MoS2 composite (abbreviated as MNF) exhibits a low overpotential (eta(10)) of 190 mV; a low Tafel slope of 31 mV dec(-1); and more importantly, a high stability in its performance manifested by the delivery of current output for 45 h. It is important to note that this could be achieved with an exceedingly low loading of 0.14 mg cm(-2). The mass activity of this composite (97 A g(-1)) is about 14 times greater than that of the conventional RuO2 (7 A g(-1) ) at eta = 200 mV. When normalized with respect to the total metal content, a mass activity of 1000 A g(-1) (eta = 300 mV) was achieved. Impedance analysis further reveals that the significant reduction in charge-transfer resistance and hence high current density (5 times greater as compared to NiFe LDH at eta = 300 mV) observed for MNF is associated with interfacial adsorption kinetics of intermediates (R-1). Significant enhancement in the intrinsic activity of MNF over LDH has been observed through normalization of current with the electrochemically active surface area. Computational studies suggest that the Ni centers in the composite act as the active sites for OER, which is well-corroborated with the observed postreaction appearance of Ni3+ species.
Keywords: Impedance; LDH-MoS2 hybrid electrocatalyst; mass activity; OER; overpotential

Influence of support textural property on CO2 to methane activity of Ni/ SiO2 catalysts - Cherevotan, Arjun; Ray, Bitan; Churipard, Sathyapal R.; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Applied Catalysis B-Environmental, 2022)
In this work, we elucidated the role of physicochemical textural properties of inert support on the catalyst ac-tivity by impregnating Ni on ordered mesoporous silica (SBA-15 and MCM-41) and non-mesoporous silica (nMPS). The catalyst Ni/SBA-15 exhibited the best CO2 conversion (83%) and product selectivity (99.9 %) followed by Ni/MCM-41 and the least by Ni/nMPS. The difference in the nature of the catalyst, degree of nanoparticle distribution and nanoparticle encapsulation by different silica support were studied by N2 adsorption-desorption and X-ray photoelectron spectroscopy (XPS) experiments. The Operando Diffused Reflec-tance Infrared Fourier Transform Spectroscopy were used to understand the variance in reaction pathway which is accredited to the textural properties of the support. The SBA-15 supported Ni catalyst followed dissociative CO pathway while MCM-41 and nMPS reacted through associative formate mechanism as major pathway. These findings provide a novel perspective on CO2 hydrogenation over Ni-silica, allowing us to tune both activity and selectivity.
Keywords: CO2 methanation; DRIFTS; Mesoporous silica support; Textural properties

Intrinsic charge polarization in Bi19S27Cl3 nanorods promotes selective C-C coupling reaction during photoreduction of CO2 to ethanol - Das, Kousik; Das, Risov; Riyaz, Mohd; Parui, Arko; Bagchi, Debabrata; Singh, Ashutosh Kumar; Singh, Abhishek Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (Advanced Materials, 2023)
Obtaining multi-carbon products via CO2 photoreduction is a major catalytic challenge involving multielectron-mediated C-C bond formation. Complex design of multicomponent interfaces that are exploited to achieve this chemical transformation, often leads to untraceable deleterious changes in the interfacial chemical environment affecting CO2 conversion efficiency and product selectivity. Alternatively, robust metal centers having asymmetric charge distribution can effectuate C-C coupling reaction through the stabilization of intermediates, for desired product selectivity. However, generating inherent charge distribution in a single component catalyst is a difficult material design challenge. Here, a novel photocatalyst, Bi19S27Cl3, is presented which selectively converts CO2 to a C-2 product, ethanol, in high yield under visible light irradiation. Structural analysis through transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy reveals the presence of charge polarized bismuth centers in Bi19S27Cl3. The intrinsic electric field induced by charge polarized bismuth centers renders better separation efficiency of photogenerated electron-hole pair. Furthermore, charge polarized centers yield better adsorption of CO* intermediate and accelerate the rate determining C-C coupling step through the formation of OCCOH intermediate. Formation of these intermediates is experimentally mapped by in situ Fourier-transform infrared spectroscopy and further confirmed by theoretical calculation.
Keywords: C-C coupling; charge polarization; CO2 reduction; Ethanol; Photocatalysis